Digital storytelling and the production of the personal in Lwandle, Cape Town - Sykes, Pam (University of Western Cape, 2020)
Philosophiae Doctor - PhD === Digital storytelling is a workshop-based practice, originally developed by the Californiabased nonprofit StoryCenter, in which people create short, first-person digital video narratives based on stories from their own lives. The practice has been adopted around the world as a participatory research method, as a pedagogical tool, as a community-based reflective arts practice and as medium for advocacy. It is associated with a loosely connected global movement linked by genealogy and a set of ethical commitments to the significance of all life stories and to the power of listening as a creative and political act.